Duri Dalam Daging Sebagai Sumber Resiliensi: Kajian Teologis 2 Korintus 12:1–10 bagi Gereja dan Pendidikan Agama Kristen - Paat, Devrialdo Daniel; Ratulangi, Andrea Elfata (Peneliti.net, 2026)
This study explores the concept of the thorn in the flesh in 2 Corinthians 12:1–10 as the foundation for developing a theology of resilience, an understanding of faith that views human weakness as the very space where God’s grace operates. The research applies a qualitative library-based approach using textual analysis through Gordon Fee and Douglas Stuart’s historical-critical hermeneutic method. It integrates Edith Grotberg’s resilience framework (I Am, I Have, I Can) with Paul’s Christology of weakness, forming a theological model that interprets suffering not as the absence of God, but as a process of spiritual formation. The findings reveal that human frailty becomes an instrument through which divine power strengthens faith and nurtures spiritual endurance. Practically, this theology of resilience provides valuable insights for pastoral ministry, Christian religious education, and the development of the church as a resilient and compassionate community capable of accompanying believers through global crises.